PERANCANGAN APLIKASI SCRAMBEL WORD GAME UNTUK MENINGKATKAN KEMAMPUAN BAHASA INGGRIS ANAK SEKOLAH DASAR BERBASIS ANDROID MENGGUNAKAN ALGORITMA BREADHT FIRST SEARCH - Dhana Hervia Siregar; Siti Sundari; Khairunnisa Khairunnisa (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
English has played an important role in life, apart from being an international language that can connect globally, English has also become an added value in the world of work. The design of the scrambled word game application for elementary school children is expected to help increase vocabulary and encourage children to concentrate more and be able to think critically. The design of this Scrambled Word Game application uses the Breadth First Search (BFS) algorithm, where the BFS algorithm will carry out a search to determine the goal to be achieved. It can be seen from the results of the questionnaire that was distributed to 20 respondents that 85% stated "Agree" that this Scrambled word game can help to improve the English language skills of elementary school children, especially in terms of vocabulary and word understanding.